Radiation Monitoring and Dose Estimation of the Fukushima Nuclear Accident - Takahashi, Sentaro (Springer Nature, 2014)
Effects of Radiation/Radiation Protection; Environmental Health; Nuclear Energy; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Nuclear Chemistry; Fukushima nuclear plant accident; Environmental contamination by radionuclides; Radiation dose assessment; Aerial radiation dose; Environmental monitoring